The importance of relative humidity for telenomus remus (Hymenoptera: Platygastridae) parasitism and development on Corcyra cephalonica (Lepidoptera: Pyralidae) and Spodoptera frugiperda (Lepidoptera: Noctuidae) eggs - Pomari-Fernandes, Aline; Queiroz, Ana Paula de; Bueno, Adeney de Freitas; Sanzovo, Allisson Wilson; Bortoli, Sergio Antonio de [UNESP] (Oxford Univ Press Inc, 2015)
The rearing of Telenomus remus (Nixon 1937) has been limited due to the difficulty of its development in its natural host, the eggs of Spodoptera frugiperda (J.E. Smith). Environmental conditions can strongly affect egg's parasitoid rearing on factitious hosts; however, until now only the effects of temperature have been studied. The importance of relative humidity in T. remus parasitism is poorly understood; therefore, this study evaluated its parasitism on Corcyra cephalonica (Stainton, 1866) and S. frugiperda eggs under different humidity regimes. Lifetime parasitism and parasitism viability were higher on S. frugiperda eggs and did not differ among humidity regimes. However, these biological parameters were higher at 80% humidity than at both 40 and 60% humidity when T. remus was reared on C. cephalonica eggs. The sex ratio was always higher than 0.6 for all hosts and humidity regimes. Parental female longevity was only influenced by humidity when presented to C. cephalonica eggs: it was higher at 60 and 80% humidity. T. remus egg-to-adult period was longer in C. cephalonica eggs; however, no difference between humidity regimes was noted. In general, relative humidity affected T. remus development only when it was reared on C. cephalonica eggs. For this factitious host, 80% humidity was shown to be appropriate for egg parasitoid rearing due to its better biological performance.
Keywords: Factitious host; Biological control; Egg parasitoid; Parasitoid rearing